Labor Theory of Value, Value and Price: A Historical Meeting between Chinese and Western Marxist Scholars: Commentary on Volume 2 of “Normative and Empirical Research on Labor Creating Value” by Cheng Enfu et al. (World Marxist Review, 2025)
This is the second of two volumes comprising The Creation of Value by Living Labour: A Normative and Empirical Study. The first opened with a review of the literature on labor’s role in production, laying the ground, as the work’s title suggests, for a detailed empirical study of creative, scientific, and management labour in China, conceived of as an economy with mixed forms of property.Its central concern was how best to maximize the social and economic benefits of these highly productive forms of labour, extending these benefits to the whole of society by preventing their monopolization and misuse by property-owners.The present volume underpins that analysis with a detailed discussion of the Marxist literature on the relation between labor, value and price. This may come as a surprise to both neoclassical scholars and to Marxist and other heterodox scholars. Why do Chinese economists consider a Victorian ‘minor post-Ricardian’, as Samuelson (1957, 911) derisively labelled Marx, relevant to the economy of the modern powerhouse that is China? And why should Westerners pay any attention to Chinese discussions of obscure sixty-year-old debates, riddled with mathematical subtleties and apparently confined to the ivory towers?To answer this question, it is necessary to turn it upside down. It has come to the attention of the world that China’s economic successes, for a long time overlooked or dismissed by Western writers, are without precedent. No country has sustained a growth rate so large for so long, or raised so many people out of extreme poverty in a mere thirty years. No nation of any size except South Korea has achieved Chinese levels of development since the epoch of high imperialism. Even were China’s growth to stop tomorrow, its economic achievements to date would be unparalleled in the history of capitalism.